Gas sensing properties of WO3-doped ZnO nanoparticles synthesized by flame spray pyrolysis - Chawarat Siriwong (2018)
The flame-made (5/5) pure ZnO and WO3-doped ZnO nanoparticles containing 0.25, 0.50, and 0.75 mol% of WO3 were successfully synthesized by flame spray pyrolysis (FSP). These materials were studied for NO2, CO and H2 gas sensing at different gas concentrations and operating temperatures ranging from 300-400°C in dry air. The crystalline phase, morphology and size of the nanoparticles were characterized by XRD, BET, TEM, SEM and EDS in order to correlate physical properties with gas sensing performance. The gas-sensing results showed that WO3 doping significantly enhanced NO2 gassensing performance of ZnO nanoparticles. In addition, 0.5 mol% is found to be an optimal WO3 concentration which gives the highest sensitivity towards NO2. ©2009 IEEE.